2017
DOI: 10.3130/jaabe.16.201
|View full text |Cite
|
Sign up to set email alerts
|

Semi-active Outrigger Damping System for Seismic Protection of Building Structure

Abstract: The outrigger structural system is one of the most widely used lateral load-resisting structural systems for high-rise buildings. To increase the energy dissipation capacity of the outrigger system, an outrigger damping system has been proposed as a novel energy dissipation system. In this system, the outrigger and perimeter columns are separate and vertical viscous dampers are equipped between the outrigger and perimeter columns. In this study, the control performance of a semi-active outrigger damping system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This intended damper by authors is compared with electromagnetic transducers and found that the designed damper system is effective in vibration reduction for time history analysis. As MR damper has proved to be a promising device in structural control, in the article [100], a fuzzy logic algorithm is combined with genetic algorithm optimization for reducing the outrigger structural response. From this study, the displacement of the structure excited for an earthquake is shown in Fig.…”
Section: Development Of Outrigger Structural System From Tall Buildingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This intended damper by authors is compared with electromagnetic transducers and found that the designed damper system is effective in vibration reduction for time history analysis. As MR damper has proved to be a promising device in structural control, in the article [100], a fuzzy logic algorithm is combined with genetic algorithm optimization for reducing the outrigger structural response. From this study, the displacement of the structure excited for an earthquake is shown in Fig.…”
Section: Development Of Outrigger Structural System From Tall Buildingsmentioning
confidence: 99%
“…13 Integrated steel amplification devices with viscous damper [93] Fig. 14 Displacement of structure without and with outrigger and semi-active outrigger [100] damping system and semi-active dampers regulated by different control algorithms to enhance the outrigger structural behavior.…”
Section: Development Of Outrigger Structural System From Tall Buildingsmentioning
confidence: 99%
“…(xviii) According to reference [186], using the distributed belt wall system as virtual outriggers is effective in reducing lateral drift of tall buildings as much as the conventional belt and outrigger structure. (xix) According to reference [187], the semiactive outrigger damping system can reduce both displacement and acceleration responses considerably compared to the conventional outrigger system. (xx) According to reference [188], the outrigger tuned inertial mass electromagnetic transduce (TIMET) improves energy generation efficiency to a large extent with the input energy to the structure kept low.…”
Section: Optimum Topology and Size Of Outrigger And Belt-truss Systemmentioning
confidence: 99%
“…Where the semi active device investigated the seismic response in a building using fuzzy control algorithm. The artificial seismic load was generated for numerical simulation for outrigger MR Damping model [62].…”
Section: Figure 28 Control Object In the Topmentioning
confidence: 99%